Evaluation of a Care Coordination Measure for the Consumer Assessment of Healthcare Providers and Systems (CAHPS®) Medicare Survey. (April 2014) - Hays, Ron D.; Martino, Steven; Brown, Julie A.; Cui, Mike; Cleary, Paul; Gaillot, Sarah; Elliott, Marc
There is widespread interest in assessing care coordination to improve overall care quality. We evaluated a five-item measure of care coordination included in the 2012 Consumer Assessment of Healthcare Providers and Systems (CAHPS) Medicare survey ( n = 326, 194 respondents, 46% response rate). This measure includes patient reports of whether their personal doctor discusses their medicines, has medical records and other relevant information, and is informed about care from specialists, and whether the patient gets help in managing care and timely follow-up on test results. A one-factor categorical confirmatory factor analytic model indicated that five items constituted a coherent scale. Estimated health-plan-level reliability was 0.70 at about 102 responses per plan. The composite had a strong unique association with the CAHPS global rating of health care, controlling for the CAHPS core composite scores. This measure can be used to evaluate relative plan performance and characteristics associated with better care coordination.